Polyethylene glycol-chitosan oligosaccharide-coated superparamagnetic iron oxide nanoparticles: A novel drug delivery system for curcumin diglutaric acid - Feuangthit Niyamissara Sorasitthiyanukarn (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Curcumin diglutaric acid-loaded polyethylene glycol-chitosan oligosaccharide-coated superparamagnetic iron oxide nanoparticles (CG-PEG-CSO-SPIONs) were fabricated by co-precipitation and optimized using a Box–Behnken statistical design in order to achieve the minimum size, optimal zeta potential (≥ ±20 mV), and maximum loading efficiency and capacity. The results demonstrated that CG-PEG-CSO-SPIONs prepared under the optimal condition were almost spherical in shape with a smooth surface, a diameter of 130 nm, zeta potential of 30.6 mV, loading efficiency of 83.3%, and loading capacity of 8.3%. The vibrating sample magnetometer results of the optimized CG-PEG-CSO-SPIONs showed a superparamagnetic behavior. Fourier transform infrared spectroscopy and X-ray diffraction analyses indicated that the CG physically interacted with PEG-CSO-SPIONs. In addition, the CG-PEG-CSO-SPIONs could be stored dry for up to 12 weeks or in aqueous solution for up to 4 days at either 4 °C or 25 °C with no loss of stability. The CG-PEG-CSO-SPIONs exhibited a sustained release profile up to 72 h under simulated physiological (pH 7.4) and tumor extracellular (pH 5.5) environments. Furthermore, the CG-PEG-CSO-SPIONs showed little non-specific protein binding in the simulated physiological environment. The CG-PEG-CSO-SPIONs enhanced the cellular uptake and cytotoxicity of CG against human colorectal adenocarcinoma HT-29 cells compared to free CG, and more CG was delivered to the cells after applying an external magnetic field. The overall results suggest that PEG-CSO-SPIONs have potential to be used as a novel drug delivery system for CG.